Pre-Service EFL Teachers' Perception of Using Facebook Group for Learning - Purnamasari, Asri (JET (Journal of English Teaching), 2019)
The current development of ICT has been revolutionizing education. The revolution has now overflown learning beyond the four walls boundary of the classroom. By using ICT, students today can learn anytime and anywhere. This study aimed to explore pre-service EFL teachers' perception of the use of Facebook Group (FBG) in learning. Employed a mixed methods research designed, quantitative and qualitative data were collected from 56 (29 first-year and 27 second-year) students of the English Education Department of Universitas Kristen Indonesia Jakarta using a questionnaire and interview. The finding revealed that the majority of the participants had positive perception towards using FBG as a learning platform. However, since their experience in the informal language learning environment through FBG was new, their view towards the use of FBG for interpretative communication activates was lower than for interpersonal communication.